2003
DOI: 10.1080/15622970310029916
|View full text |Cite
|
Sign up to set email alerts
|

Creatine kinase BB in brain in schizophrenia

Abstract: Creatine kinase (CK) is responsible for the creatine/creatine phosphate level which that is known to alter in the brain of patients with schizophrenia. A comparative estimation of CK enzymatic activity and immunoreactivity of CK BB was carried out in readily soluble extracts from frontal cortex, anterior and posterior cingulate cortex, hippocampus and cerebellum from brains of individuals with schizophrenia versus normal controls. CK activity was determined using a commercial diagnostic kit. CK BB immunoreacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…39 A spot corresponding to CK-Mit was not visualized in a sufficient amount of the schizophrenia ACC gray matter gels, in agreement with the literature detailing a reduced level of CK-Mit in post-mortem schizophrenia tissue. 30,42 This data suggest neuronal energy depletion, possibly glutamatergic. Synaptic filling of glutamatergic cells would also be adversely affected by a loss of CK-Mit in the ACC in schizophrenia.…”
Section: Metabolismmentioning
confidence: 78%
See 1 more Smart Citation
“…39 A spot corresponding to CK-Mit was not visualized in a sufficient amount of the schizophrenia ACC gray matter gels, in agreement with the literature detailing a reduced level of CK-Mit in post-mortem schizophrenia tissue. 30,42 This data suggest neuronal energy depletion, possibly glutamatergic. Synaptic filling of glutamatergic cells would also be adversely affected by a loss of CK-Mit in the ACC in schizophrenia.…”
Section: Metabolismmentioning
confidence: 78%
“…However, activity of CKB is thought to be reduced in the frontal cortex, anterior and posterior cingulate, hippocampus and cerebellum in schizophrenia. 42 These conflicting data may be due to the location of CKB to subsets of cells 38,39 which are differentially affected in schizophrenia. CK-Mit, located on the membrane of neurons is involved in the generation of ATP 43 and possibly glutamate filling into synaptic vesicles.…”
Section: Metabolismmentioning
confidence: 99%
“…In this context, it is known that a diminution of creatine kinase activity may potentially impair energy homeostasis, contributing to brain damage [27]. Moreover, creatine kinase inhibition has also been observed in neurodegenerative and mental diseases, such as Alzheimer's disease, schizophrenia [45] and animal models of some inborn errors of metabolism affecting the brain [46]. MacDonald et al [47] presented very interesting results, showing that levels mRNA of creatine kinase are decreased in bipolar disorder patients, especially in the hippocampus.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…Moreover, some evidences suggest changed levels of highenergy phosphates in the cortex of schizophrenic patients [79]. Burbaeva et al [45] also showed that creatine kinase was altered in the brain of patients with schizophrenia, suggesting that this decrease leads to disturbances in brain energy metabolism and is involved in the pathogenesis of this disorder.…”
Section: Schizophreniamentioning
confidence: 99%
“…Previous studies have indicated that BBCK is one of the targets of oxidative stresses induced by dis- eases or toxins. Particularly, BBCK inactivation by cystine and cystine dimethyl ester (CDME) has been observed by in vivo studies [6][7][8][9]21,22], while the other CK isoforms seem not to be affected during the pathogenesis of cystinosis [23]. The in vivo studies suggest that cystine or CDME may affect enzyme activity by the induction of free radicals and lipoperoxidation production, the increase of carbonylation of proteins and the decrease of thiol/disulfide ratio [24].…”
Section: Introductionmentioning
confidence: 99%